“A Fierce Tempest”: Disaster and Relief at the Luna Settlement, 1559–61 - Bolte, Christina L. (The Northern Mariner / Le marin du nord, 2025)
Disaster relief efforts for early colonial North America demonstrate that remote locations and the delayed response time of communications and relief supplies directly affected the success or failure of early settlement efforts. This is particularly evident for the 1559 to 1561 Tristán de Luna y Arellano colonization attempt on Pensacola Bay. After just over a month, a hurricane struck the settlement in September 1559, destroying seven ships in Luna’s fleet and much of the colony’s food stores. This research presents an analysis of the disaster relief efforts undertaken in the hope of sustaining the colony.